Modelos multivariados dinâmicos: análise de contágio nos mercados de derivativos agropecuários - Mól, Anderson Luiz Rezende (2006)
The present papers makes an analysis of identification on the evidence of Volatileness transmission and contagion in the futures market of the Brazilian agricultural commodities, in specific, coffee and beef market. It is analyzed, therefore, the hypothesis of contagion existence and it is tested starting from the estimate of multivariate models volatility. Having evidence of the breaking structural existence in the volatíleness structure of the commodities historical series of beef and coffee and such breaking could be associated with the financial crises, suggests contagion evidence. The resulte gotten in this thesis supply evidence favorable to the contagion hypothesis.